"Happy Professional Development at an Unhappy Time": Learning to Teach for Historical Thinking in a High-Pressure Accountability Context. (3rd April 2017) - Meuwissen, Kevin W.
Abstract: Adolescent learners stand to benefit when history teachers center their practice on investigating open-ended questions, interrogating evidence, and constructing persuasive arguments. Taking up this kind of teaching requires professional development (PD) experiences that are sustained, subject-specific, learning-focused, and collaborative and that provide participants with opportunities to try out, discuss, and rethink new teaching practices in an intellectually nourishing environment. Yet such experiences and the history teaching that demands them can be stifled by accountability mechanisms that discourage both. Using Hochberg and Desimone's theoretical framework for PD in accountability contexts, this comparative case study addresses how 2 teachers experienced the confluence of situational factors and facilitators in their efforts to adapt and enact PD-supported history teaching practices that conflicted with high-stakes state- and district-level accountability pressures. I suggest that PD in historical investigation and interpretation must deliberately and transparently reconcile the school-contextual constraints that challenge its effectiveness on practice. Findings also underscore divergent interpretations of what ends PD in accountability contexts ought to serve and how it should serve them.